FRI0126 Aiming for remission according to any of the rheumatoid arthritis disease activity indices is more important for physical function than the actual choice of index: a longitudinal analysis in a clinical practice setting (meteor cohort). (15th June 2017) - Carvalho, PD; Ferreira, R; Landewé, R; Vega-Morales, D; Salomon-Escoto, K; Veale, DJ; Silva, J da; Machado, PM
Abstract : Background: The association between remission and disability in patients with rheumatoid arthritis (RA) has been established mainly in clinical trial cohorts and not in "real-life" patients. Moreover, only a limited number of remission definitions have been tested. Objectives: To compare the association between different remission criteria and physical function in patients with RA followed in clinical practice. Methods: Longitudinal data from the METEOR database were used. Fifteen definitions of remission were tested: ACR-EULAR boolean-based; Simplified Disease Activity Index (SDAI); Clinical Disease Activity Index (CDAI); Disease Activity Score (DAS) and 28-joint count DAS (DAS28), both with ESR/CRP, with 3/4 variables (3v/4v), and various cut-offs tested. Disability was measured by the Health Assessment Questionnaire (HAQ) and HAQ≤0.5 was defined as a good outcome. Associations were investigated using generalised estimating equations (GEE), using HAQ≤0.5 as dependent variable and the various remission criteria as independent variables. Potential confounding factors (age, body mass index, gender, rheumatoid factor positivity, erosions and biologic treatment) were also tested. Sensitivity analyses were performed using first visits only and using patients with no missing data for all definitions of remission. Results: Data from 32, 915 patients and 157, 899 visits were available. The most stringent definition of remission (table 1 ) was the ACR-EULAR boolean definition (4.5%). The proportion of patients with HAQ≤0.5 among patients in remission was higher for the most stringent definitions. However, this also meant that, for the most stringent criteria, many patients in non-remission had HAQ≤0.5. The strongest degree of association between remission and HAQ≤0.5 was observed for the SDAI. However, only minor differences were noted between definitions (table 1 ). Sensitivity analyses yield similar results (not shown). Conclusions: The various remission definitions confirmed their validity in terms of physical function in a large international clinical practice setting. However, many patients in non-remission will still have good functional status and being in clinical remission does not equate to having HAQ≤0.5. A multidimensional approach should be taken to help patients achieve this functional goal. Achievement of remission according to any of the indices is more important than the use of a specific index. Disclosure of Interest: None declared